Karakteristik Anatomi dan Histologi Batang serta Daun Tumbuhan Perdu Suku Tumbuhan Rubiaceae, Asparagaceae, dan Rutaceae - Nadia Anastasya; Ermayanti Ermayanti (SENTRI: Jurnal Riset Ilmiah, 2025)
Shrubs are commonly used as ornamental plants in the surrounding environment, yet studies on their anatomical characteristics particularly those of local species remain limited. This research examines the stem and leaf anatomy of three shrub species from different plant families: Nusa Indah (Rubiaceae), Hanjuang Merah (Asparagaceae), and Kembang Brokoli Kuning (Rutaceae). Using a qualitative descriptive method through histological observation, free‐hand sections were prepared for stem cross-sections and leaf paradermal slices. Observation parameters included stem tissue composition, epidermal cell form, stomatal type and distribution, and trichome characteristics. The results revealed distinct anatomical differences among the three families, which constitute the novelty of this study. Rubiaceae and Rutaceae showed open collateral vascular bundles, whereas Asparagaceae exhibited a concentric amphivasal type, a structural marker typical of monocots. Leaf epidermal cells also varied, with Rubiaceae showing wavy anticlinal walls, Asparagaceae presenting straight anticlinal walls, and Rutaceae having contrasting straight (adaxial) and wavy (abaxial) patterns. Stomatal distribution differed across species, with hypostomatic leaves in Rubiaceae and amphistomatic leaves in Asparagaceae and Rutaceae. Trichomes were found only in Rubiaceae, indicating a potential adaptive trait absent in the other families. These findings contribute to expanding anatomical references for local shrubs and provide comparative diagnostic characteristics useful for botanical identification and future anatomical studies of ornamental shrub species.